Advanced Nanoparticle Coatings for Stabilizing Layered Ni‐Rich Oxide Cathodes in Solid‐State Batteries. (24th February 2022) - Ma, Yuan; Teo, Jun Hao; Walther, Felix; Ma, Yanjiao; Zhang, Ruizhuo; Mazilkin, Andrey; Tang, Yushu; Goonetilleke, Damian; Janek, Jürgen; Bianchini, Matteo; Brezesinski, Torsten
Abstract: Improving the interfacial stability between cathode active material (CAM) and solid electrolyte (SE) is a vital step toward the development of high‐performance solid‐state batteries (SSBs). One of the challenges plaguing this field is an economical and scalable approach to fabricate high‐quality protective coatings on the CAM particles. A new wet‐coating strategy based on preformed nanoparticles is presented herein. Nonagglomerated nanoparticles of the coating material (≤ 5 nm, exemplified for ZrO2 ) are prepared by solvothermal synthesis, and after surface functionalization, applied to a layered Ni‐rich oxide CAM, LiNi0.85 Co0.10 Mn0.05 O2 (NCM85), producing a uniform surface layer with a unique structure. Remarkably, when used in pelletized SSBs with argyrodite Li6 PS5 Cl as SE, the coated NCM85 is found to exhibit superior lithium‐storage properties ( q dis  ≈  204 mAh gNCM85 −1 at 0.1 C rate and 45 ° C) and good rate capability. The key to the observed improvement lies in the homogeneity of coating, suppressing interfacial side reactions while simultaneously limiting gas evolution during operation. Moreover, this strategy is proven to have a similar effect in liquid electrolyte‐based Li‐ion batteries and can potentially be used for the application of other, even more favorable, nanoparticle coatings. Abstract : A new coating strategy using preformed nanoparticles dispersed in a liquid solvent is developed to improve the cycling performance and stability of layered Ni‐rich oxide cathodes in thiophosphate‐based solid‐state batteries.